Are Foreign Investors Afraid Of State Ownership? - Thi, Quynh Nga Nguyen; Tran, Quoc Trung (UI Scholars Hub, 2021)
State ownership may help firms have better access to credit and lower financing costs but it also results in “double agency” problem. This paper investigates whether foreign investors are afraid of investing in firms with state ownership. Our research sample includes 4,079 firm-years from 567 firms listed in Vietnamese stock markets during the period 2008-2017. We employ probit and tobit models to examine how state ownership determines foreign investors’ likelihood to invest and investment magnitude respectively. Furthermore, we continue to examine how an increase in state ownership changes foreign ownership. We find that firms with higher state ownership have lower foreign ownership. Besides, an increase in state ownership reduces foreign ownership. These findings imply that foreign investors tend to avoid investing in firms with high state ownership due to their concern for “double agency” problem.